Improvisar y deliberar en incertidumbre (2015)
ABSTRACT: This article aims to infer a hypothesis about the evolution of moral decision as an automatic response. The automatism in moral decision represents two forms of know-how in nature that have allowed humans to improvise under uncertainty: the first refers to the cumulative evolution allowing natural learning execution of moral behavior and the second is the accumulated life experience in making decisions that manifests and intuitions and emotions updated whenever humans faces a problem of moral choice.